2012
DOI: 10.1007/s10396-012-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography with Sonazoid™ for the evaluation of bowel ischemia

Abstract: Contrast-enhanced ultrasonography with Sonazoid™ is a highly sensitive and specific method for the diagnosis of bowel ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Sonographic findings suggesting the need for surgery include intraperitoneal free fluid, bowel wall thickness > 4 mm, decreased or absent peristalsis in documented mechanical obstruction, absence or reduced bowel wall perfusion at Doppler sonography or with IV contrast-enhanced ultrasound (CEUS) and, in advanced stages free intraperitoneal gas indicating bowel perforation [27,35,[49][50][51]. However, after the encouraging preliminary results with the use of firstgeneration contrast agents, no further studies have confirmed whether CEUS can accurately detect ischemia in the presence of bowel strangulation [52][53][54]. Currently the authors acknowledge that these GIUS signs have low accuracy in predicting complicated SBO associated with critical ischemia and therefore CT scanning plays a more crucial role for this purpose.…”
Section: Sonographic Signs Of Complicationmentioning
confidence: 99%
“…Sonographic findings suggesting the need for surgery include intraperitoneal free fluid, bowel wall thickness > 4 mm, decreased or absent peristalsis in documented mechanical obstruction, absence or reduced bowel wall perfusion at Doppler sonography or with IV contrast-enhanced ultrasound (CEUS) and, in advanced stages free intraperitoneal gas indicating bowel perforation [27,35,[49][50][51]. However, after the encouraging preliminary results with the use of firstgeneration contrast agents, no further studies have confirmed whether CEUS can accurately detect ischemia in the presence of bowel strangulation [52][53][54]. Currently the authors acknowledge that these GIUS signs have low accuracy in predicting complicated SBO associated with critical ischemia and therefore CT scanning plays a more crucial role for this purpose.…”
Section: Sonographic Signs Of Complicationmentioning
confidence: 99%
“…Intestinal ischaemia (IIS) is a potentially fatal event caused by various diseases and characterised by a rapidly progressive course leading to intestinal necrosis, both in humans and animals. [1][2][3][4] Acute arterial mesenteric thromboembolism secondary to hypertrophic cardiomyopathy, 3,5 trauma-associated mesenteric ischaemia, 6 bowel strangulation and ischaemia secondary to foreign body obstruction 7 have been reported in the veterinary literature. Clinical presentation is non-specific and includes vomiting and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…3 In humans, the gold standard for diagnosis of IIS is abdominal CT angiography (sensitivity: 82-96%; specificity: 94%) or magnetic resonance angiography. 1,2,[8][9][10][11] Abdominal ultrasonography (US) is commonly used in human and small animal patients with acute abdomen; however, this technique is not accurate when evaluating IIS. 1,2,5,8,12 Conventional Doppler US is not suitable for the evaluation of intestinal micro-perfusion because flow velocity and amplitude are too low to be detected, even in a normal intestine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations